Influencia de la altura del tocón en la capacidad y longitud del rebrote de Calycophyllum spruceanum en zona aluvial, Iquitos-2022 - Padilla Castro, Jose Luis (2024)
The area where the study was carried out is located in the Moena Caño Community, located on the left bank of the Amazon River, Maynas Province, Belén District, Loreto Region. The present study analyzes the influence of stump height on the capacity and length of the regrowth of Calycophyllum spruceanum in an alluvial zone of the Peruvian Amazon. The parametric tests between the stump height and the study variables were done using the analysis of variance for a completely randomized design with an unequal number of observations per treatment and the Tukey test at 95% confidence. The results indicate a capacity and length of the regrowth of Calycophyllum spruceanum classified as bad. Parametric tests show that none of the applied cutting heights show real differences in terms of regrowth capacity and length. It is recommended to evaluate additional variables such as the age and diameter of the trees, stump diameter, basal regrowth diameter, intervention technique and site conditions to obtain a greater amount of information. It is still premature to rule out the species Calycophyllum spruceanum for production as coppice due to its low capacity and poor regrowth development; other variables such as stump diameter need to be